2019
DOI: 10.1109/access.2019.2948868
|View full text |Cite
|
Sign up to set email alerts
|

Dual Notch Microwave Sensors Based on Complementary Metamaterial Resonators

Abstract: In this paper, three dual notch microwave sensors are presented based on a microstrip transmission line and complementary metamaterial resonators. The main aim of this paper is to compare the constitutive parameters and sensitivity of all three dual notch sensors which are based on complementary symmetric split ring resonator (CS-SRR), complementary asymmetric split ring resonator (CAS-SRR) and complementary bisymmetric split ring resonator (CBS-SRR). The main motivation beyond the presented work is to use dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…e magnetic field's stored energy is typically equal to the energy stored due to the electric field at the resonance frequency. Conversely, the magnetic and electric fields form a new resonance by altering the material under test (MUT) insertion on or near the resonator depending on the variation in permittivity, permeability, and MUT volume [33]. In this study, the MUT was introduced on the sensor covering its entire surface, as shown in Figure 9, where MUT can be termed as an overlayer.…”
Section: Validation Of Sensormentioning
confidence: 99%
“…e magnetic field's stored energy is typically equal to the energy stored due to the electric field at the resonance frequency. Conversely, the magnetic and electric fields form a new resonance by altering the material under test (MUT) insertion on or near the resonator depending on the variation in permittivity, permeability, and MUT volume [33]. In this study, the MUT was introduced on the sensor covering its entire surface, as shown in Figure 9, where MUT can be termed as an overlayer.…”
Section: Validation Of Sensormentioning
confidence: 99%
“…Recently reported dual band sensors are based on MTL with magnetically coupled SRRs or electrically coupled CSRRs. These sensors have a sensitivity limitation due to the low Q factor and poor coupling between the MTL and the resonator [29][30][31]. In [29], a dual notch microwave sensor based on MTL and two SRRs is presented that is operating at 2.34 GHz and 2.74 GHz, and a maximum Q factor of 137 is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…But the features come with a limitation of poor capacitive coupling effect and reduces the sensitivity. Besides, reported articles [25][26][27] has large geometry since resonating principle and architecture is based on size of the resonator. Therefore, prospective application field of the microwave sensors become incompatible for small scale integration.…”
Section: Introductionmentioning
confidence: 99%